2016
DOI: 10.1111/aos.13285
|View full text |Cite
|
Sign up to set email alerts
|

OPA1 analysis in an international series of probands with bilateral optic atrophy

Abstract: OPA1 gene screening in patients with bilateral optic atrophy is an important part of clinical evaluation as it may establish correct clinical diagnosis. Our study expands the spectrum of OPA1 mutations causing dominant optic atrophy and supports the fact that haploinsufficiency is the most common disease mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The present study has some limitations: first of all, we used a small simple size and there was disproportionate distribution in DOA groups, but the haploinsufficiency is the most common disease mechanism (Liskova et al 2017) and our sample confirms it. However, DOA is a rare disease, and the OPA1 missense mutations are less frequently found.…”
Section: Discussionmentioning
confidence: 74%
“…The present study has some limitations: first of all, we used a small simple size and there was disproportionate distribution in DOA groups, but the haploinsufficiency is the most common disease mechanism (Liskova et al 2017) and our sample confirms it. However, DOA is a rare disease, and the OPA1 missense mutations are less frequently found.…”
Section: Discussionmentioning
confidence: 74%
“…This non-conservative change can lead to destabilization of the protein structure resulting in decreased protein function. In fact, numerous articles have reported that the change is associated with optic atrophy 1 [24,25]. In addition, computational prediction tools unanimously predict a deleterious effect on the gene, and its frequency in gnomAD population databases is extremely low.…”
Section: Oft-00786mentioning
confidence: 99%